2009
DOI: 10.1007/s12519-009-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Foreskin development in 10 421 Chinese boys aged 0–18 years

Abstract: Incomplete separation of foreskin is common in children. Since it is a natural phenomenon to approach the adult condition until puberty, circumcision should be performed with cautions in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
1
12
0
3
Order By: Relevance
“…These rates are higher when evaluating children aged 1-9 years, of whom 5.8% were circumcised in a 9-year period. These numbers are similar to what was previously reported: 5 to 10% of children required circumcision (9,10) . It is important to reinforce that there are several difficulties and limitations for people who seek a specialist in SUS (11) .…”
Section: Discussionsupporting
confidence: 91%
“…These rates are higher when evaluating children aged 1-9 years, of whom 5.8% were circumcised in a 9-year period. These numbers are similar to what was previously reported: 5 to 10% of children required circumcision (9,10) . It is important to reinforce that there are several difficulties and limitations for people who seek a specialist in SUS (11) .…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, the prepuce is unretractable in almost 100% of infants vs. less than 5% of children approaching puberty. [5,6] The reasons for improvement are as follows: 1) The prepuce is sensitive to androgens and the preputial outlet becomes wider once testosterone production starts; 2) In all neonates the skin is fused to the glans (balano-preputial adhesions) and the skin detaches as the latter produces a substance known as smegma, that accumulates between the skin and glans. The accumulating smegma can form "white cysts" under the skin that often prompt surgical consultation, but in fact do not need any treatment.…”
Section: Review Articlementioning
confidence: 99%
“…The separation of the prepuce/glans penis mucosa is usually complete by about 17 years of age. Studies have confirmed that preputial non-separation (adhesions) is very common in children and teenagers but resolves over time [3,6,7].…”
mentioning
confidence: 95%
“…Religious circumcision is practiced in the Jews and the Muslims. Definite medical indications for circumcision in children include pathological phimosis; paraphimosis; recurrent balanitis; Balanitis Xerotica Obliterans (BXO); recurrent urinary tract infections (UTI) and benign and malignant lesions of prepuce [3]. In Japan and Canada [4,5], surgeons do not advocate routine neonatal circumcision while studies from Sub-Saharan Africa report increased acceptance of circumcision.…”
mentioning
confidence: 99%